Learning to Write Poetry Text using Project Based Learning Method with the Help of Powtoon Media - Imas Sukaesih (JLER (Journal of Language Education Research), 2022)
ABSTRACTThe number of students who experience scores below the KKM in writing learning is the background for carrying out this research. Problem based learning (PBL) methods and powtoon media are used in poetry text learning to provide solutions to these problems. The purpose of this study was to find out the results and difficulties experienced by students while participating in poetry text learning using the problem based learning (PBL) method with the help of powtoon media. The research method used is descriptive qualitative. Data collection techniques used are observation sheets and test sheets. The results showed that as many as 81.82% of students were able to get a score above the KKM and there were 18.18% of students still having difficulties. The difficulty of students is in the use of diction aspects when writing poetry texts, it is known from getting the lowest score in each aspect, which is only getting 43 points. But overall the problem based learning (PBL) method with powtoon media in poetry text learning has a positive impact on student achievement.ABSTRAKBanyaknya siswa yang mengalami nilai dibawah KKM pada pembelajran menulis menjadi latar belakang dilaksanakan penelitian ini. Metode problem based learning (PBL) dan media powtoon digunakan pada pembelajaran teks puisi untuk memberikan solusi dari permasalah tersebut. Tujuan penelitian ini untuk mencari tahu hasil dan kesulitan-kesulitan yang dialami siswa selama mengikuti pembelajaran teks puisi menggunaan metode problem based learning (PBL) dengan bantuan media powtoon . Metode penelitian yang digunakan yaitu deksriptif kualitatif. Teknik pengambilan data yang digunakan yaitu lembar observasi dan lembar tes. Hasil penelitian menunjukan bahwa sebanyak 81,82% siswa mampu memperoleh nilai diatas KKM dan terdapat 18,18% siswa masih mengalami kesulitan. Kesulitan siswa terdapat pada penggunaan aspek diksi saat menulis teks puisi hal tersebut diketahui dari peroleh nilai terendah pada setiap aspeknya yaitu hanya mendapatkan 43 point saja.  Tetapi secara keseluruhan metode problem based learning (PBL) dengan media powtoon pada pembelajaran teks puisi memberi dampak positif dalam pencapaian prestasi belajar siswa.